Vaccine hesitancy among mobile pastoralists in Chad: a qualitative study - Mahamat Fayiz Abakar; Djimet Seli; Filippo Lechthaler; Esther Schelling; Nhan Tran; Jakob Zinsstag; Daniel Cobos Muñoz (BMC, 2018)
Abstract Background Demand side barriers to vaccination among rural and hard-to-reach populations in Chad are not yet well understood. Although innovative approaches such as linking human and animal vaccination increase vaccination uptake among mobile pastoralist communities, vaccination coverage in these communities is still lower than for rural settled populations. We hypothesize that mobile pastoralists' communities in Chad face specific demand side barriers to access vaccination services. Understanding the factors that caregivers in these communities consider, explicitly or implicitly, in order to decide whether or not to vaccinate a child, in addition to understanding the provider's perspectives, are essential elements to tailor vaccination programmes towards increasing vaccination acceptance and uptake. Methods We conducted a qualitative study in a rural health district in southern Chad in April 2016 with 12 key informant in-depth interviews and four focus group discussions (FGDs) including 35 male and female participants. Participants in the study included caregivers, traditional chiefs, local and religious leaders from mobile pastoralist communities, and health officials and staff. We conducted a content analysis using a pre-defined set of categories for vaccine hesitancy covering issues on harmful effects of vaccination, mistrust with vaccination programmes/services, issues with the health system and other issues. Results The groups of demand side barriers reported most frequently in focus group discussions were mistrust on the expanded programme on immunization (EPI) and polio vaccination outreach services (53%, n = 94), followed by health system issues (34%, n = 94), and concerns related to potential harm of vaccines (13%, n = 94). Concerns identified by caregivers, health professionals and community leaders followed a similar pattern with issues on programme mistrust being most frequently reported and issues with harm least frequently reported. None of the health professionals reported concerns about vaccinations being potentially harmful. Conclusion Mobile pastoralist communities face specific demand side barriers to vaccination. Understanding these barriers is essential to reduce vaccine hesitancy and increase vaccination uptake. Local health systems must plan for the periodic presence of pastoralist communities in their zones of responsibility and create more mutual trust.